A selective turn-off fluorescence detection of nitroexplosive 2, 4, 6-trinitrophenol by pyridinium-based chemosensor in pure aqueous medium. (September 2020) - Saini, Vaishali; Gupta, Aman; Rangan, Krishnan; Khungar, Bharti
Abstract: A chemosensor 1-(2-(6-oxobenzo [4, 5]imidazo [1, 2- c ]quinazolin-5(6H)-yl)ethyl)pyridin-1-ium bromide (BZQZPy ) bearing benzimidazo-quinazolinone and pyridinium moieties has been developed for the nanomolar detection of 2, 4, 6-trinitrophenol (TNP) in aqueous medium. BZQZPy exhibited excellent cyan blue fluorescence that is quenched on the addition of TNP via turn-off fluorescence response. The UV–visible, fluorescence and 1 H NMR spectroscopy, lifetime measurements and theoretical calculations suggested that ground state charge transfer complex formation and energy transfer mechanisms are possible causes for this fluorescence quenching. BZQZPy is highly sensitive and selective towards TNP with high quenching constant (K sv ) of 1.53 × 10 4  M −1 and low detection limit of 20 nM. The proposed chemosensor is also applicable for the on-site determination of TNP on filter paper and in real water samples. Graphical abstract: A pyridinium-based chemosensor exhibiting a highly selective fluorescent turn-off response towards 2, 4, 6-trinitrophenol up to nM level in water was developed. Image 1 Highlights: Synthesis of pyridinium-based chemosensor employing simple methodologies. The chemosensor showed a highly selective and sensitive detection of 2, 4, 6-trinitrophenol (TNP) in aqueous medium up to nM level. The sensing mechanism was deduced by experimental and theoretical studies. TNP detection was also performed on filter paper test strips and in real water samples.